ANALISIS DAMPAK INFLASI TERHADAP DAYA BELI MASYARAKAT - Herlambang, Muhammad Farhan; Pratiwi, Regina; Naila Zain; Hasibuan, Reni Ria Armayani (Kampus Akademik Publiser, 2026)
This research aims to analyze the impact of inflation on the purchasing power of the community. This study uses a qualitative approach through interviews and literature studies as secondary data. The results conclude that inflation has a proven negative effect on the purchasing power of the community, especially low-income groups and small business actors. At a broader level, high and uncontrolled inflation can widen social disparities and reduce welfare, as the poor bear a heavier burden than high-income groups. Overall, these findings emphasize that inflation control must be accompanied by policies to protect purchasing power so that economic stability goes hand-in-hand with social justice and welfare.